Recent Advances in Tetrakis (4‐Carboxyphenyl) Porphyrin‐Based Nanocomposites for Tumor Therapy. Issue 3 (30th December 2022) - Xie, Yulin; Wang, Man; Sun, Qianqian; Wang, Dongmei; Li, Chunxia
Abstract : Cancer has always been a terrible disease threatening human life. Although many researches have been carried out on cancer, there is still no way to cure it. Emerging therapeutic methods, such as photodynamic therapy (PDT), photothermal therapy (PTT), and immunotherapy, have brought the dawn for tumor treatment. As a typical photosensitizer (PS), tetrakis (4‐carboxyphenyl) porphyrin (TCPP) is favored by researchers. TCPP itself has powerful performance, which can be modified and coupled to obtain nanotherapeutic agents with excellent therapeutic effects. What's more, metal–organic frameworks (MOFs) seem tailor‐made for the TCPP. MOFs with stable structure, large surface area, and aperture structure give TCPP more potential for application. With this in mind, the researches of TCPP‐based nanocomposites in tumor therapy in recent years are summarized, and the challenges in the tumor therapy of TCPP‐based nanocomposites and possible research directions to achieve highly efficient therapeutic effects are discussed. Abstract : Tetrakis (4‐carboxyphenyl) porphyrin (TCPP) has powerful performance, which can be modified and coupled to obtain nanotherapeutic agents with excellent therapeutic effects. As a member of the porphyrin family, TCPP has been widely used in material design for cancer therapy. Herein, the latest reports on TCPP‐based nanocomposites in cancer treatment are collected and a classification analysis is conducted.